65‐1: Invited Paper: Enhanced Efficiency of InP‐based Red and Green Quantum‐Dot Light‐emitting Diodes. Issue 1 (25th September 2020) - Li, Yanzhao; Li, Dong; Kristal, Boris; Feng, Jingwen; Lu, Zhigao; Chen, Zhuo; Li, Xinguo
Abstract : Due to the inherent toxicity of cadmium selenide (CdSe)‐based quantum dots (QDs), Cd‐free alternatives are being widely investigated. Indium phosphide (InP) QDs have shown great potential as a replacement for CdSe QDs in display applications. However, the performance of InP‐based quantum dot light emitting diodes (QLEDs) is still far behind that of the CdSe‐based devices. In this study, we wanted to show the effects of different approaches to improve the performance of InP‐based QLED devices. We investigated the effect of magnesium (Mg) doping in ZnO nanoparticles, which is used as an n‐type electron transport layer, in balancing the charge transfer in InP‐based QLED devices. We found that an increasing Mg doping level can broaden the ZnO band gap, shift its energy levels, but most importantly, increase its resistivity; as a result, the electron current density is significantly reduced and the device efficiency is improved. We also investigated the effect of high‐photoluminescence quantum yield emitters and different QLED architectures on the device performance. Through optimizing QD structures and devices, red InP QLEDs with the current efficiencies reaching 11.6 cd/A and green InP QLEDs with the current efficiencies reaching 37.0 cd/A were fabricated.